2018
DOI: 10.1007/978-981-10-8016-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Delay and Cost Overrun in Malaysian Construction Industry

Abstract: The construction industry in Malaysia drives the economic growth and development of the country. However, the industry is plagued with delays and cost overrun which transforms what should have been successful projects to projects incurring additional costs, disagreements, litigation and in some cases abandonment of projects. This research studied the causes of delays and cost overrun in the industry and ranked them according to their perceived importance to the contractors, with a view to establishing those to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…In Malaysia, the main causes of cost overruns and delays in building construction projects are poor scheduling and control of time; delays in the preparation of design documents; ineffective communication between stakeholders; changes in laws and regulations; low labour productivity; lack of knowledge in executing methods (Tahir, Haron, Alias & Diugwu, 2017: 1); contractor's financial problems that result in the shortage of construction materials on-site; owner's financial problems and slowness in decisionmaking; consultant's poor supervision and delays in issuing instructions, and external factors such as materials shortage and poor site condition (Musa, 2012: 5).…”
Section: Causes and Implications Of Megaproject Delays And Cost Overrunsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Malaysia, the main causes of cost overruns and delays in building construction projects are poor scheduling and control of time; delays in the preparation of design documents; ineffective communication between stakeholders; changes in laws and regulations; low labour productivity; lack of knowledge in executing methods (Tahir, Haron, Alias & Diugwu, 2017: 1); contractor's financial problems that result in the shortage of construction materials on-site; owner's financial problems and slowness in decisionmaking; consultant's poor supervision and delays in issuing instructions, and external factors such as materials shortage and poor site condition (Musa, 2012: 5).…”
Section: Causes and Implications Of Megaproject Delays And Cost Overrunsmentioning
confidence: 99%
“…The results in Table 4 show that these factors could contribute to project implementation sluggishness in South Africa. A study by Tahir et al (2017: 3) indicated that the project teams' slow rate in making decisions is one of the causes of delay that could contribute to project implementation sluggishness. The issues identified in this instance are indicative of project management teams that are either overwhelmed or not sufficiently knowledgeable.…”
Section: Ranking Of the Factors Causing Schedule Overrunmentioning
confidence: 99%
See 1 more Smart Citation
“…The quest to assuage the threat of a construction delay, coupled with its negative effects, has necessitated myriads of investigations over the years, which are predominantly directed towards identifying factors responsible for this monumental problem. Tahir et al (2019), for example, investigated the causes of a delay and cost overrun in Malaysian construction projects, while Gardezi et al (2014) investigated time extension factors in the Pakistani construction industry. The study results show key delay factors, such as law and order situation, design changes, and improper availability of funds with the client.…”
Section: Introductionmentioning
confidence: 99%
“…, India, Iran, Malaysia, New Zealand, Nigeria, Norway, Turkey, the UK, and KazakhstanAmeh and Osegbo (2011),Kazaz et al (2012),Aziz (2013),Desai and Bhatt (2013),Gascuena et al (2011),Hickson and Ellis (2014),Lessing et al (2017),Moradi et al (2017), European Commission (2018),Karthik and Rao (2018),Zidane and Andersen (2018),Hossain et al (2019),Tahir et al (2019),Ardila and Francis (2020…”
mentioning
confidence: 99%